Dampak Pt Bintan Karisma Pratama Pada Perubahan Sosial Ekonomi Masyarakat Nelayan Pesisir : (Studi Kasus Pulau Telang Kecil Kecamatan Mantang Kabupaten Bintan Kepulauan Riau) - Daniati Daniati; Desi Ratnasari; Azizah Azizah; Vivi Fitriani; Maya Gustiani Putri; Ella Selselviana; Sri Wahyuni (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The research aims to determine the impact of PT. Bintan Karisma Pratama which is located on Telang Island, Mantang District, Bintan Regency in the Riau Islands Province, on community life in Telang Kecil village with economic and social aspects of community life and how this PT contributes to local or local communities after the compensation assistance provided by PT for the Telang Kecil community, this research uses qualitative methods, namely in the form of interview and observation techniques or field studies, as well as literature studies to support the results of this research. The impact of PT Bintan Karisma Pratama on the environment of the people of Telang Kecil does not have a serious impact because the PT has first assessed the location area where it wants to be established and has followed the rules of the decision-making process regarding business and activity organizers or what is known as AMDAL, the marine environment of Telang Kecil is also categorized. Clean, local people are able to take good care of the marine environment. The majority of their livelihoods are fishermen and others work as workers at Pt Bintan Karisma Pratama, wives work as housewives and there are also those who work as small traders or small food and beverage businesses.